BUYUK IPAK YO‘LIDA JOYLASHGAN QADIMIY SHAHARLAR TARIXI - G’ayratova Nozigul, Qosimova Dinora (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the emergence, formation, branches, historical significance, and cultural influence of the Great Silk Road. The article provides information on how the cities located along the Silk Road can strengthen trade relations with each other and develop them.